Penguatan Majelis Ekonomi PCM Jebres Melalui Peningkatan Nilai Produk Pengusaha Binaan PCM Jebres - Sholahuddin, Muhammad; Lestari, Wuryaningsih Dwi; Padmantyo, Sri; Irawati, Zulfa; Nasir, Moechammad; Kuswati, Rini; Saputro, Edy Purwo; Murwanti, Sri (Prosiding University Research Colloquium, 2022)
This activity is a community service carried out in the City of Jebres for a micro-enterprise (UMKM) with the business name PCM Jebres. The spread of COVID-19 that hit Indonesia directly had a negative impact on micro-enterprises in Indonesia, especially in the City of Jebres. The implementation of Large-Scale Social Restrictions (PSBB) by both central and regional governments significantly reduces consumer access to these micro-enterprises. The purpose of this community service is to increase the entrepreneurial knowledge and skills of business owners in selling through social networking media. The method of implementation includes the first stage of socialization and preparation, the second stage is the circumcision of materials, the third stage is the implementation, the fourth stage is monitoring and evaluation then the last stage is the preparation of scientific reports and publications. Results obtained after mentoring show an increase in partners' understanding of the P-IRT submission process. This activity is expected to be an example for other micro-businesses affected by the COVID-19 pandemic and be a solution to the existing MSME problem. This service has been implemented socialization of P-IRT submission program in January. Based on the results of the evaluation before and after the event, participants already understand how the P-IRT submission process. Participants have filled out the official adjutant form of socialization of surakarta health office. Among the requirements is a photo of yourself. Participants who do not have a photo of themselves are directly helped in the photo at the place of activity. The next activity is adjutant technical guidance to the Surakarta Health Office and uploading P-IRT adjutant.